Prostate specific membrane antigen binding radiopharmaceuticals: Current data and new concepts - Sartor, Oliver; Baghian, Ali (Frontiers in Medicine, 2022)
Prostate specific membrane antigen (PSMA) represents a validated target for prostate cancer therapeutics. The phase III VISION study with 177lutetium (177Lu)-PSMA-617 represented a pivotal step forward and the FDA has now approved this agent in advanced metastatic castrate-resistant prostate cancer (mCRPC). A number of other PSMA targeted radiopharmaceuticals are now under development. Some of these agents are targeted to PSMA via monoclonal antibodies such as J591 and TLX591. Others are targeted to PSMA via small molecules such as PSMA-617, PSMA I&T, MIP-1095, etc. In addition to the use of various ligands, multiple isotopes are now in clinical trials. Beta emitters in development include 177Lu, 131iodide (131I), and 64copper (64Cu). Targeted alpha emitters potentially include 225actinium (225Ac), 227thorium (227Th), and 212lead (212Pb). Phase III trials are underway with both 177Lu-PSMA-617 and 177Lu-PSMA I&T in mCRPC. Single dose phase I trials are complete with 225Ac-J591 but additional data are need to launch a phase III. Data are promising with 225Ac-PSMA-617 but concerns remain over salivary and renal toxicity. Tandem therapies are also considered combining both beta and alpha targeted therapy. Taken together the field of PSMA targeted radiopharmaceuticals is rapidly developing. The targeted alpha therapies are particularly promising and several developmental paths forward are being considered in the near future.